الإدارة ونظرية التقوى (دراسة قرآنية تحليلية): Management and Theory of Taqwa (An Analytical Quranic Study) - KURT, Nurullah; M Alfarsi, Samira; Ahmad Fadzillah, Nurrulhidayah (Online Journal of Research in Islamic Studies, 2021)
The Islamic nation in particular, and human society in general, are experiencing moral, tyrannical, exclusionary and other crises of various kinds of injustice and contempt that fall on more than one actor in various fields of life. Hence, the research came to show management and the theory of Taqwa in the Holly Qur’an and the Sunnah Al-Nabawyyiah, this is based on the principle that management based on Taqwa is a historical fact that Muslims lived for a long period of time. The study relied on the analytical method. Among the most important findings of this study; That there is no decent life for the Islamic nation without administration based on Taqwa and observing God Almighty, as it was in the era of the Prophet, peace be upon him, and the honorable Companions, may God be pleased with them, and that administrative work in the Islamic system in all its forms and forms is a great responsibility that requires great effort and devotion from the responsible person. Likewise, with its holistic theory, Islam provided a concept of management that comprehends all human life affairs, and that Islamic action could not have any effective role in bringing the ummah to the position of " You are the best nation produced [as an example] for mankind " except in the light of management based on Taqwa and observing God Almighty.